2021
DOI: 10.30880/jtmb.2021.08.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Construction Safety and Performance in Malaysian Construction Industry: A Review

Abstract: Major construction projects in Malaysia are subjected to unsafe conditions that can result in accidents and subsequently undermine the project’s safety results. Despite alarming, studies examining thefactors that influence the performance of the Malaysianconstruction industryremain scarce. Hence, this paper aims to review the literature related to construction safety performance in the Malaysian construction industry. In particular, thispaper givesemphasis in reviewing the literature on constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Safety is a multidisciplinary topic that involves different fields, such as economics, psychology, industrial technology, law, and occupational hygiene among others. Many safety issues in construction projects have been overlooked due to the authorities' primary concern of completing as many activities as possible (Sultan et al, 2021). The construction industry is considered a highly dangerous risk activity in Malaysia.…”
Section: Lack Of Safety Concernmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety is a multidisciplinary topic that involves different fields, such as economics, psychology, industrial technology, law, and occupational hygiene among others. Many safety issues in construction projects have been overlooked due to the authorities' primary concern of completing as many activities as possible (Sultan et al, 2021). The construction industry is considered a highly dangerous risk activity in Malaysia.…”
Section: Lack Of Safety Concernmentioning
confidence: 99%
“…Personal protective equipment should be provided by the company at zero cost to the employee, and workers should not work in an unsanitary or hazardous environment. (Sultan et al, 2021) Regular inspection of job site material and equipment and identified the equipment by tagging or locking the controls to render them inoperable. Besides that, communication barriers are broken down and transparency between managers and journal.ump.edu.my/jgi ◄ employees is encouraged by a good safety culture.…”
Section: Lack Of Safety Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…Major construction projects in Malaysia are susceptible to hazardous conditions that can result in accidents, jeopardizing the overall safety outcomes of the project. However, there is a notable scarcity of research on the safety predictors influencing the safety performance of the construction field in Malaysia (Albarkani & Shafii, 2021). The impact of safety compliance and safety participation on safety performance is significant and requires attention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Bangladesh, the construction sector contributes nearly 8% of the country's GDP [13 -15]. Therefore, the success of the construction companies impacts the development of the economies of the countries [16]. Considering the value of engineering, the productivity and profitability of construction companies depend on time, cost, quality, and safety [17 -20].…”
Section: Introductionmentioning
confidence: 99%